Analysis of the strategic development of small and medium-sized businesses in the Rostov region ("Journal "U". Economy. Management. Finance.", 2019)
This article analyzes the strategic development of entrepreneurship in the small and medium sectors of the Rostov region. The basis of the study was the dynamics of the number of subjects for the period 2016-2018, identifying problems that impede its development, as well as their solutions. The aim of the work is to analyze the development of commercial organizations of small and medium sizes in the Rostov Region, identify current problems in this area and identify strategic directions of movement.
Keywords: small and medium enterprises; strategy; promotion of entrepreneurship; Rostov region; Problems; development; region; project; analysis